2006
DOI: 10.1590/s0006-87052006000200012
|View full text |Cite
|
Sign up to set email alerts
|

Formação de mudas de cafeeiro em substratos oriundos de diferentes métodos de desinfestação

Abstract: Objetivando verificar o desenvolvimento de cafeeiro oriundos de diferentes métodos de tratamento de substratos utilizados na produção de mudas em saquinhos de polietileno, instalou-se em maio/2004 em um viveiro na Universidade Federal de Lavras o presente experimento. Foram utilizados treze tratamentos para a desinfestação de substratos, sendo utilizado o padrão para mudas de café com solo coletado de uma lavoura cafeeira de 20 anos. Utilizou-se a cultivar paraíso H 419-1. Avaliou-se o crescimento das plantas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
1
3
0
1
Order By: Relevance
“…These results were also verified by Miranda et al (2006) who reported that coffee seedlings cultivar Paraíso H 419-1 showed growth retardation in the 15-day solarization treatment. In the work developed by Cruz (2020), a different behavior is observed, as there is no significant change in the weight of plant matter in an experiment evaluated in cabbage plants, planted in treated substrate and untreated in a solarizer.…”
Section: Discussionsupporting
confidence: 80%
“…These results were also verified by Miranda et al (2006) who reported that coffee seedlings cultivar Paraíso H 419-1 showed growth retardation in the 15-day solarization treatment. In the work developed by Cruz (2020), a different behavior is observed, as there is no significant change in the weight of plant matter in an experiment evaluated in cabbage plants, planted in treated substrate and untreated in a solarizer.…”
Section: Discussionsupporting
confidence: 80%
“…The vegetative growth of coffee plants was evaluated at 7, 21, 35, 49, and 63 days after application (DAA) of the herbicide. The parameter evaluated were: plant height, from the stem base to the meristematic apex; stem base diameter, measured with a caliper (Miranda et al, 2006); number of sprouts; and total leaf area (TLA) Leite;Ferreira, 2008), measured using the equations: Leaf area (LA) = leaf length × leaf width × 0.663 (correction factor), and TLA = ∑LA. One plant per plot was collected for this destructive analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Desta forma, a inoculação com espécies de FMA, favorece o crescimento das mudas (PouyuRojas e Siqueira, 2000), aumenta a tolerância ao estresse provocado pelo transplantio, aumenta o índice de sobrevivência após o transplantio, além de reduzir o tempo para formação da muda no viveiro (Miranda et al, 2006). O alto potencial do uso de fungos micorrízicos na formação de mudas de cafeeiro é caracterizado pela elevada dependência micorrízica do cafeeiro, principalmente, em solos de baixa fertilidade (Colozzi Filho et al, 1994).…”
Section: Introductionunclassified